Can students themselves narrow the socioeconomic-status-based achievement gap through their own persistence and learning time? - Huang, Haigen (Education Policy Analysis Archives, 2015)
Despite decades of educational reforms, the achievement gap based on socioeconomic status (SES) persists in the United States. Not only does the SES-based achievement gap persist, it has also been widening. This study focused on the role of students, hypothesizing that students might reduce the SES-based achievement gap by increasing their learning time and persistence. I used both ANOVA and two-level hierarchical linear models (HLM) to analyze the Program for International Student Assessment (PISA) United States data. The findings suggested that students viewing themselves to be persistent were likely to perform better than those viewing themselves to be less persistent. Also increased time learning in school was associated with increased achievement. However, high-SES students generally spent more time learning in school and viewed themselves to be more persistent. Thus learning time and persistence were not likely to address the SES constraint on achievement for a majority of low-SES students unless schools provided them extra classes and learning opportunities.